Effect of Tax Administration on Tax Revenue of States in African Countries: Evidence from Nigeria - Azende, Terungwa; Ganyam, Amos Iorcher (International Journal of Business, Economics and Management, 2020)
This study assessed the effect of tax administration on tax revenue of states in African countries with specific reference to Nigeria. The extent of improvement in tax revenue generated by states in Nigeria due to the change in tax administration motivated this study. Data were obtained from the Nigerian National Bureau of Statistics (NBS) and analyzed using the descriptive statistics and paired samples t-test statistics. Findings revealed a significant mean difference in pay-as-you-earn (PAYE) and road taxes (RT) before and during the tax administration of 2015 by Nigerian states. Findings also revealed an insignificant mean difference in direct assessment (DA) and miscellaneous taxes (MT) before and during the tax administration of 2015 by Nigerian states. The study concluded that the change in tax administration only witnessed selective improvement on tax revenue generated by the states and recommended that the state boards of internal revenue should consistently carry out tax awareness programs in their various states so as to enlighten the self-employed persons and informal business owners on the need and benefits of tax payment.